Influence of composite mix and praticle content on the strength and sorption properties of calamus deerratus composites (2013)
"The influence of composite mix and particle content on the strength and sorption properties of Calamus deerratus composites was investigated. Experimental rattan cement board were made from C.deerratus particles of 1.18mm,cement: sand ratios of 1:2 and 1:3 and 5% and 10% rattan contents. Fabricated boards were tested after 28 days for strength and sorption properties. Results obtained showed that the strength properties reduced while the sorption properties increased with increase in rattan content and cement: sand ratio. The composites were however suitable for low stressed indoor and outdoor applications. "